Natural photocatalyst with ultrahigh specific surface area as well as preparation method and application thereof
By placing seaweed in heavy metal contaminated water and preparing a natural photocatalyst with ultra-high specific surface area, the existing photocatalysts have small surface area and poor degradation effect when treating organic dye wastewater, and achieving efficient and environmentally friendly organic dye removal effect.
Patent Information
- Application Number
- CN202411847081.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When existing photocatalysts treat organic dye wastewater, the surface area is small, resulting in poor adhesion and fixation effects of pollutants and unsatisfactory degradation effects.
By placing seaweed in heavy metal-contaminated water, endogenous metal-rich seaweed was obtained, and a natural photocatalyst with ultra-high specific surface area was prepared through steps such as segmented pore reaming and chemical regulation treatment.
The prepared natural photocatalyst has a developed pore structure and an ultra-high specific surface area, which significantly improves the removal effect of organic dyes, with a removal rate of more than 90%, and has no secondary pollution, and is suitable for industrial applications.
Smart Images

Figure CN119657233A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sewage treatment, and in particular to a natural photocatalyst with ultra-high specific surface area and a preparation method and application thereof. Background Art
[0002] Cationic dye compounds, as a typical organic dye pollutant, are widely used in printing, textile, leather, wool and other industries. Even at very low concentrations, dye-containing wastewater poses a serious threat to human health and the ecosystem. Therefore, the treatment technology of dye wastewater has become a difficulty and focus of wastewater treatment research. In the past few decades, a series of studies have been conducted on the removal of dyes from wastewater, including physical adsorption, chemical oxidation, membrane separation, biological treatment, photocatalytic degradation and electrochemical methods. However, the high cost, secondary pollution, complex process and high energy consumption of these methods limit their widespread application. Therefore, the development of low-cost, strong adsorption and high degradation efficiency photocatalysts to catalyze the decomposition of organic pollutants is a top priority in solving problems in the field of sewage treatment.
[0003] Biochar is a carbonaceous material, which is a porous solid carbon-rich material obtained by pyrolysis of a large amount of raw biomass, such as sawdust, straw, rice husk and bamboo, under complete or partial anoxic conditions. Biochar with a high specific surface area can adsorb, stabilize or catalyze organic pollutants through surface electrostatic effects and void filling. Therefore, how to obtain biochar with a high specific surface area is one of the research hotspots. It is worth noting that compared with terrestrial biomass, seaweed contains relatively rich elements such as calcium (Ca), magnesium (Mg), iron (Fe), potassium (K), manganese (Mn), copper (Cu) and zinc (Zn), which are conducive to the efficient transfer of electrons and the synergistic effect of multiple catalytic centers, thereby creating potential conditions for it to become a catalytic material that can provide high stability and unique electronic properties. At present, there is no research and report on the preparation of natural photocatalysts using seaweed.
[0004] The research on the preparation of photocatalysts and their degradation of organic dye wastewater in related technologies is as follows:
[0005] Chinese patent CN102423717A discloses a highly efficient photocatalyst for degrading organic dyes, wherein the Bi-TiO2 / SBA-15 photocatalyst is prepared by using tetrabutyl titanate, anhydrous ethanol, citric acid, polyethylene glycol and an emulsifier; Chinese patent CN102600865A discloses a photocatalyst for degrading organic dye wastewater pollutants and a preparation method thereof, wherein the photocatalyst is a composite of magnesium ferrite and silver vanadate nanoparticles, and the general chemical composition formula is: mMgFe2O4 / Ag3VO4, where m is the mass ratio of MgFe2O4 to Ag3VO4, and 0<m≤0.005; Chinese patent CN1036412 31A discloses an application of a visible light catalyst copper borate to degrade dye wastewater. Copper borate Cu3B2O6 can be used as a visible light catalyst to catalyze the degradation of organic dye wastewater under visible light; Chinese patent CN118341465A discloses a preparation method of a solid Z-type heterojunction Fe2O3 / g-C3N4 photocatalyst for degrading dye wastewater, and a solid Z-type heterojunction Fe2O3 / g-C3N4 photocatalyst for degrading dye wastewater is prepared by a one-step reaction; Chinese patent CN118343881A discloses a simple, efficient and green method for visible light driven anthraquinone and its derivatives to catalyze the degradation of organic pollutants.
[0006] The photocatalyst used in the above-mentioned organic dye treatment method has a small specific surface area, is not easy to attach and fix pollutants, and has a poor degradation effect on organic dyes. Summary of the invention
[0007] In view of this, the purpose of the present invention is to provide a natural photocatalyst with ultra-high specific surface area and its preparation method and application. The natural photocatalyst prepared by the present invention has a large specific surface area, is easy to attach and fix pollutants, and has a good organic dye degradation effect.
[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0009] The present invention provides a method for preparing a natural photocatalyst with an ultra-high specific surface area, comprising the following steps:
[0010] The seaweed is placed in a heavy metal polluted water body for cultivation to obtain seaweed rich in endogenous metals;
[0011] Expanding the endogenous metal-rich seaweed in sections to obtain a preliminary carbonized product;
[0012] The preliminary carbonization product is mixed with an activator and then subjected to chemical regulation treatment to obtain a carbonization product;
[0013] The carbonized product is washed and dried in sequence to obtain the natural photocatalyst.
[0014] Preferably, the heavy metal elements in the heavy metal-contaminated water body include one or more of Fe, Mn, Ni and Zn.
[0015] Preferably, the segmented hole expansion includes acid treatment and preliminary carbonization treatment in sequence, and the acid treatment includes acid immersion and hydrothermal treatment in sequence.
[0016] Preferably, the acid reagent used in the acid soaking is a hydrochloric acid solution or a nitric acid solution.
[0017] Preferably, the temperature of the hydrothermal treatment is 20 to 80° C., and the time is 12 to 24 hours.
[0018] Preferably, the temperature of the preliminary carbonization treatment is 600-1000° C., the holding time is 1-3 hours, and the heating rate from room temperature to the temperature of the preliminary carbonization treatment is 5-15° C. / min.
[0019] Preferably, the mass ratio of the activator to the preliminary carbonization product is 1 to 5:1.
[0020] Preferably, the temperature of the chemical regulation treatment is 600-1000°C, the insulation time is 1-3h, the heating rate from room temperature to the temperature of the chemical regulation treatment is 5-15°C / min, and the chemical regulation treatment is carried out in a protective atmosphere.
[0021] The present invention also provides a natural photocatalyst with ultra-high specific surface area prepared by the preparation method described in the above technical solution.
[0022] The present invention also provides the use of the natural photocatalyst with ultra-high specific surface area described in the above technical solution in the treatment of organic dye wastewater.
[0023] The present invention provides a method for preparing a natural photocatalyst with an ultra-high specific surface area, comprising the following steps: placing seaweed in a heavy metal-contaminated water body for cultivation to obtain seaweed rich in endogenous metals; performing segmented pore expansion on the seaweed rich in endogenous metals to obtain a preliminary carbonization product; mixing the preliminary carbonization product with an activator and performing chemical regulation treatment to obtain a carbonization product; and washing and drying the carbonization product in sequence to obtain the natural photocatalyst.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The present invention provides a technology for the value-added utilization of marine solid waste. Seaweed is extremely abundant in species, and due to its short growth cycle, seasonal over-breeding often occurs, aggravating the eutrophication of coastal waters and even endangering the stability of the marine ecosystem. The present invention uses marine solid waste as raw material, is suitable for the resource recycling and treatment of seaweed, reduces resource waste and environmental pollution, and achieves the purpose of "treating waste with waste".
[0026] 2. The present invention produces a natural photocatalyst with an ultra-high specific surface area. The acid pretreatment process can remove most of the impurity metal elements in the seaweed raw material and help to increase the effective content of C. In the initial carbonization process, the aliphatic alkyl chains and ester groups in the biomass begin to gradually decompose. In the chemical regulation process, taking KOH as an example, the activator is completely converted into K2CO3 and K2O, and the metallic potassium element is precipitated in the form of steam, causing the carbon layer structure to be distorted or deformed, thereby forming pores. The prepared photocatalyst has a developed pore structure and an ultra-high specific surface area, which can be used to remove pollutants in water bodies, realize the resource utilization of seaweed solid waste, and achieve the purpose of protecting the environment.
[0027] 3. The present invention places seaweed in heavy metal contaminated water for cultivation, and utilizes the excellent bioaccumulation effect of seaweed on heavy metals in heavy metal contaminated water to obtain seaweed rich in endogenous metals. The natural photocatalyst with ultra-high specific surface area prepared by the present invention is rich in endogenous mineral components, such as Fe, Ni, Mn, Zn or Ti, which can improve the graphitization level of the catalyst during the pyrolysis process, promote the formation of edge defect structures, significantly improve the electron transfer ability, greatly improve the catalytic performance of the catalyst, and is more conducive to the degradation of organic dye pollutants.
[0028] In summary, the natural photocatalyst with ultra-high specific surface area prepared by the present invention has a wide range of raw materials, low cost and renewable. The porous high specific surface area sample prepared by the three-step method of acid treatment, preliminary carbonization treatment and chemical regulation treatment can efficiently adsorb and stabilize organic pollutants; and the transition metal oxides (such as Fe2O3, TiO2, MnO2 and NiO) contained in it can effectively promote the decomposition of organic dye molecules through visible light excitation. The natural photocatalyst prepared by the present invention is a green and environmentally friendly method for removing organic dyes, which has a wide range of applications and no secondary pollution. It has a wide application prospect in industry and can solve the technical problems that the pollutants in the existing organic dye wastewater treatment are not effectively dispersed, the adsorption efficiency is low, the life is short, and it is difficult to be applied to the actual degradation of organic pollutants.
[0029] The present invention also provides a natural photocatalyst prepared by the preparation method described in the above technical solution. The data in the embodiment show that the specific surface area of the natural photocatalyst prepared by the present invention is as high as 3360.28 m 2 / g, and has a significant removal effect on organic dyes, with a removal rate of over 90%. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a SEM image of the seaweed raw material at low magnification;
[0031] Figure 2 This is a SEM image of the seaweed raw material at high magnification;
[0032] Figure 3 is a SEM image of the natural photocatalyst prepared in Example;
[0033] Figure 4 is a SEM image of a natural photocatalyst prepared in a comparative example;
[0034] Figure 5 is the N2 adsorption-desorption isotherm of natural photocatalyst A1;
[0035] Figure 6 is the pore size distribution diagram of natural photocatalyst A1;
[0036] Figure 7 This is a diagram showing the removal effect of natural photocatalysts A1~A6, D1~D4 and CB on organic dyes;
[0037] Figure 8 This is a cyclic experiment of natural photocatalyst A1 degrading methylene blue. DETAILED DESCRIPTION
[0038] The present invention provides a method for preparing a natural photocatalyst with an ultra-high specific surface area, comprising the following steps:
[0039] The seaweed is placed in a heavy metal polluted water body for cultivation to obtain seaweed rich in endogenous metals;
[0040] Expanding the endogenous metal-rich seaweed in sections to obtain a preliminary carbonized product;
[0041] The preliminary carbonization product is mixed with an activator and then subjected to chemical regulation treatment to obtain a carbonization product;
[0042] The carbonized product is washed and dried in sequence to obtain the natural photocatalyst.
[0043] In the present invention, unless otherwise specified, the raw materials used are all commercially available products in the art.
[0044] The invention places seaweed in a heavy metal polluted water body for cultivation to obtain seaweed rich in endogenous metals.
[0045] In the present invention, the heavy metal elements in the heavy metal-contaminated water body preferably include one or more of Fe, Mn, Ni and Zn.
[0046] In the present invention, the concentration of heavy metal salts in the heavy metal polluted water is preferably 10-150 mg / L; the present invention regulates the metal enrichment capacity of living seaweed by changing the concentration of heavy metal ions in the heavy metal polluted water.
[0047] In the present invention, the heavy metal polluted water body is preferably natural seawater or simulated heavy metal polluted water body. The present invention utilizes the excellent bioaccumulation effect of seaweed on heavy metals in water bodies to prepare natural endogenous metal-rich raw materials, and the endogenous mineral components rich in seaweed, such as Fe, Ni, Mn, Zn or Ti, can improve the graphitization level of the catalyst during the pyrolysis process, promote the formation of edge defect structures, significantly improve the electron transfer ability, greatly improve the catalytic performance of the catalyst, and are more conducive to the degradation of organic dye pollutants.
[0048] In the present invention, the simulated heavy metal polluted water body is preferably prepared by a method comprising the following steps: mixing a heavy metal mother liquor and a seawater f / 2 culture solution to obtain the simulated heavy metal polluted water body.
[0049] In the present invention, the heavy metal elements in the heavy metal mother solution preferably include one or more of Fe, Mn, Ni and Zn.
[0050] In the present invention, the heavy metal salt in the heavy metal mother solution preferably includes one or more of FeCl3·6H2O, MnCl2·6H2O, NiCl2·6H2O and ZnSO4·7H2O.
[0051] In the present invention, the seawater f / 2 culture medium is preferably sterilized. The present invention has no particular limitation on the specific method of the sterilization, and a method well known to those skilled in the art may be used.
[0052] In the present invention, the concentration of heavy metal salts in the heavy metal mother solution is preferably 5-170 mg / L, specifically 100, 150 or 170 mg / L. In a specific embodiment of the present invention, the concentration of heavy metal salts in the heavy metal mother solution is: FeCl3·6H2O 100 mg / L, MnCl2·6H2O 50 mg / L, NiCl2·6H2O 10 mg / L and ZnSO4·7H2O 10 mg / L; or FeCl3·6H2O 100 mg / L, MnCl2·6H2O 50 mg / L; or FeCl3·6H2O 100 mg / L.
[0053] In the present invention, the seaweed preferably includes one or more of Enteromorpha, Ulva, Laminaria japonica and Sargassum.
[0054] The present invention preferably places the heavy metal contaminated water in an incubator, and places the seaweed in the water for cultivation, wherein the incubator is set with a suitable temperature, light cycle, and light intensity, and the seaweed rich in endogenous metals is obtained through enrichment. In a specific embodiment of the present invention, the cultivation is carried out at a temperature of 25°C, a light cycle (simulating natural growth conditions to maintain normal photosynthesis of seaweed) of 12h:12h, and a light intensity of 4000lx.
[0055] The present invention has no particular limitation on the specific parameters of the culture and enrichment, and methods well known to those skilled in the art may be used.
[0056] After obtaining the seaweed rich in endogenous metals, the present invention performs segmented pore expansion on the seaweed rich in endogenous metals to obtain a preliminary carbonized product.
[0057] In the present invention, the seaweed rich in endogenous metals is preferably soaked in clean water to clean and remove scale and impurities, dried, crushed, and sieved, and then placed in a sealed bag for standby use.
[0058] In the present invention, the particle size after pulverization is preferably 40 to 100 meshes.
[0059] The present invention has no special limitation on the specific parameters of soaking with clean water for cleaning, descaling and impurity removal, drying and screening, and methods well known to those skilled in the art may be adopted.
[0060] In the present invention, the segmented hole expansion preferably includes acid treatment and preliminary carbonization treatment in sequence.
[0061] In the present invention, the acid treatment preferably includes acid soaking and hydrothermal treatment in sequence; the effect of the acid treatment is to remove most of the constant metal salts in the seaweed to obtain an "eggshell" type initial pore structure.
[0062] In the present invention, the acid reagent used in the acid soaking is preferably a hydrochloric acid solution or a nitric acid solution.
[0063] In the present invention, the concentration of the acid reagent is preferably 0.2-0.5 mol / L, specifically 0.2, 0.3, 0.4 or 0.5 mol / L.
[0064] In the present invention, the temperature of the hydrothermal treatment is preferably 20-80°C, specifically 20, 30, 40, 50, 60, 70 or 80°C, and the time is preferably 12-24h, specifically 12, 16, 18 or 24h.
[0065] After the hydrothermal treatment is completed, the present invention preferably washes the obtained product with deionized water until it is neutral, puts it into an oven for drying, and then performs the preliminary carbonization treatment.
[0066] In the present invention, the temperature of the preliminary carbonization treatment is preferably 600-1000°C, specifically 600, 700, 800, 900 or 1000°C, the insulation time is preferably 1-3h, specifically 1, 2 or 3h, and the heating rate from room temperature to the temperature of the preliminary carbonization treatment is preferably 5-15°C / min, specifically 5, 10 or 15°C / min.
[0067] In the present invention, the preliminary carbonization treatment is preferably carried out in a tubular furnace. After the preliminary carbonization treatment is completed, the obtained product is preferably cooled to room temperature in the furnace and then taken out to obtain the preliminary carbonized product.
[0068] After obtaining the preliminary carbonization product, the present invention mixes the preliminary carbonization product with an activator and then performs chemical regulation treatment to obtain a carbonization product.
[0069] In the present invention, the mass ratio of the activator to the preliminary carbonization product is preferably 1 to 5:1, specifically 1:1, 2:1, 3:1, 4:1 or 5:1.
[0070] In the present invention, the activator preferably includes one or more of KOH, NaOH, ZnCl2 and H3PO4; the function of the activator is to change the pore structure.
[0071] In the present invention, the temperature of the chemical regulation treatment is preferably 600-1000°C, specifically 600, 700, 800, 900 or 1000°C, the insulation time is preferably 1-3h, specifically 1, 2 or 3h, the heating rate from room temperature to the temperature of the chemical regulation treatment is preferably 5-15°C / min, specifically 5, 10 or 15°C / min, the chemical regulation treatment is preferably carried out in a protective atmosphere, and the protective atmosphere is preferably nitrogen.
[0072] In the present invention, the flow rate of the nitrogen gas is preferably 100 mL / min.
[0073] The present invention preferably dry-mixes the preliminary carbonization product with an activator, places the obtained mixture in a tubular furnace, and raises the temperature to the temperature of the chemical regulation treatment under nitrogen protection. After the chemical regulation treatment is completed, the obtained sample is taken out after cooling to room temperature with the furnace.
[0074] After obtaining the carbonized product, the present invention sequentially washes and dries the carbonized product to obtain the natural photocatalyst.
[0075] In the present invention, the washing is preferably carried out by acid washing and water washing in sequence, the detergent for the acid washing is preferably a hydrochloric acid solution, and the concentration of the hydrochloric acid solution is preferably 0.1 mol / L.
[0076] In the present invention, the acid washing is preferably performed three times. The present invention preferably places the carbonized product in a hydrochloric acid solution for washing, continues washing after suction filtration, and washes three times in total, and then washes with deionized water in a water bath at 80°C until the pH value of the washing solution is 6-8.
[0077] In the present invention, the drying preferably further includes ball milling. The present invention has no particular limitation on the specific parameters of the drying and ball milling, and methods well known to those skilled in the art may be used.
[0078] The present invention also provides a natural photocatalyst with ultra-high specific surface area prepared by the preparation method described in the above technical solution.
[0079] The present invention also provides the use of the natural photocatalyst with ultra-high specific surface area described in the above technical solution in the treatment of organic dye wastewater.
[0080] In the present invention, the application preferably includes the following steps: mixing the natural photocatalyst with wastewater to be treated for degradation.
[0081] In the present invention, the organic dye in the wastewater to be treated is preferably methylene blue.
[0082] In the present invention, the concentration of the organic dye in the wastewater to be treated is preferably 40 mg / L.
[0083] In the present invention, the dosage ratio of the natural photocatalyst to the wastewater to be treated is preferably 0.02 g:40 mL.
[0084] In the present invention, the degradation time is preferably 0 to 200 min, specifically 30, 60, 90, 120, 150, 180 or 200 min.
[0085] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0086] Example 1
[0087] ⑴Heavy metal enrichment process: Prepare 1L of heavy metal mother solution (concentrations: FeCl3·6H2O 100mg / L, MnCl2·6H2O 50mg / L, NiCl2·6H2O 10mg / L and ZnSO4·7H2O 10mg / L) and add it to sterilized seawater f / 2 culture medium (the content of NaNO3 in seawater f / 2 culture medium is 74.8mg / L, the content of NaH2PO4 is 4.4mg / L, and other components are not added) to obtain 10L of experimental seawater. The seaweed (EP) was placed in the experimental seawater for 5 months, and the incubator was set with appropriate temperature (25℃), light cycle (12h:12h), and light intensity (4000lx). After the enrichment process, seaweed raw materials rich in endogenous metals can be obtained.
[0088] (2) Acid treatment: Soak the salvaged Enteromorpha in clean water, remove scale and impurities, dry, crush, pass through an 80-mesh sieve, and then put it into a sealed bag for later use; soak the seaweed powder in 0.5 mol / L hydrochloric acid solution, and hydrothermally treat it at 60°C for 12 hours, wash it with deionized water until it is neutral, and put it into an oven for drying.
[0089] ⑶ Preliminary carbonization treatment: The seaweed powder was placed in a tubular furnace for carbonization, and the temperature was raised to 700°C at a heating rate of 5°C / min for carbonization for 2 hours. After cooling to room temperature, the powder was taken out to obtain a preliminary carbonized product.
[0090] (4) Chemical regulation treatment: dry-mix the preliminary carbonization product with KOH activator in a mass ratio of (1:3), place the mixture in a tubular furnace, and heat it to a carbonization final temperature of 800°C under nitrogen protection for 2 hours at a heating rate of 5°C / min and a nitrogen flow rate of 100 mL / min. Take out the sample when it cools to room temperature.
[0091] ⑸ Washing and drying: The carbonized product is placed in a hydrochloric acid solution with a concentration of 0.1 mol / L for washing, and then filtered and continued to wash for a total of three times; then washed with deionized water in a water bath at 80°C until the pH of the washing solution is 6-8, dried, and ball-milled to obtain a natural photocatalyst A1 with an ultra-high specific surface area.
[0092] Example 2
[0093] ⑴Heavy metal enrichment process: Prepare 1L of heavy metal mother solution (concentration: FeCl3·6H2O 100mg / L, MnCl2·6H2O 50mg / L) and add it to the sterilized seawater f / 2 culture medium (the NaNO3 content in the seawater f / 2 culture medium is 74.8mg / L, the NaH2PO4 content is 4.4mg / L, and other components are not added) to obtain 10L of experimental seawater. The seaweed is placed in the experimental seawater for 5 months, and the incubator is set with appropriate temperature (25℃), light cycle (12h:12h), and light intensity (4000lx). After the enrichment process, seaweed raw materials rich in endogenous metals can be obtained.
[0094] (2) Acid treatment: Soak the salvaged Enteromorpha in clean water, remove scale and impurities, dry, crush, pass through a 20-mesh sieve, and then put it into a sealed bag for later use; soak the seaweed powder in 0.2 mol / L hydrochloric acid solution, and hydrothermally treat it at 40°C for 12 hours, wash it with deionized water until it is neutral, and put it into an oven for drying.
[0095] ⑶ Preliminary carbonization treatment: The seaweed powder was placed in a tubular furnace for carbonization, and the temperature was raised to 1000°C at a heating rate of 15°C / min for carbonization for 2 hours. After cooling to room temperature, it was taken out to obtain a preliminary carbonized product.
[0096] (4) Chemical regulation treatment: dry-mix the preliminary carbonization product with KOH activator in a mass ratio of (1:1), place the mixture in a tubular furnace, and heat it to a carbonization final temperature of 800°C under nitrogen protection for 2 hours at a heating rate of 5°C / min and a nitrogen flow rate of 100 mL / min. Take out the sample when it cools to room temperature.
[0097] ⑸ Washing and drying: The carbonized product is placed in a 0.1 mol / L hydrochloric acid solution for washing, and then filtered and continued to wash for a total of three times; then washed with deionized water in a 80°C water bath until the pH of the washing solution is 6-8, dried, and ball-milled to obtain a natural photocatalyst A2 with an ultra-high specific surface area.
[0098] Example 3
[0099] ⑴Heavy metal enrichment process: Prepare 1L of heavy metal mother solution (concentrations: FeCl3·6H2O 100mg / L, MnCl2·6H2O 50mg / L, NiCl2·6H2O 10mg / L and ZnSO4·7H2O 10mg / L) and add it to sterilized seawater f / 2 culture medium (the content of NaNO3 in seawater f / 2 culture medium is 74.8mg / L, the content of NaH2PO4 is 4.4mg / L, and other components are not added) to obtain 10L of experimental seawater. The seaweed is placed in the experimental seawater for 5 months, and the incubator is set with appropriate temperature (25℃), light cycle (12h:12h), and light intensity (4000lx). After the enrichment process, seaweed raw materials rich in endogenous metals can be obtained.
[0100] (2) Acid treatment: Soak the salvaged Enteromorpha in clean water, remove scale and impurities, dry, crush, pass through a 60-mesh sieve, and then put it into a sealed bag for later use; soak the seaweed powder in 0.5 mol / L hydrochloric acid solution, and hydrothermally treat it at 50°C for 12 hours, wash it with deionized water until it is neutral, and put it into an oven for drying.
[0101] ⑶ Preliminary carbonization treatment: The seaweed powder was placed in a tubular furnace for carbonization, and the temperature was raised to 600°C at a heating rate of 5°C / min for carbonization for 2 hours. After cooling to room temperature, the powder was taken out to obtain a preliminary carbonized product.
[0102] (4) Chemical regulation treatment: dry-mix the preliminary carbonization product with KOH activator in a mass ratio of (1:1), place the mixture in a tubular furnace, and heat it to a carbonization final temperature of 800°C under nitrogen protection for 2 hours at a heating rate of 5°C / min and a nitrogen flow rate of 100 mL / min. Take out the sample when it cools to room temperature.
[0103] ⑸ Washing and drying: The carbonized product is placed in a hydrochloric acid solution with a concentration of 0.1 mol / L for washing, and then filtered and continued to wash for a total of three times; then washed with deionized water in a water bath at 80°C until the pH of the washing solution is 6-8, dried, and ball-milled to obtain a natural photocatalyst A3 with an ultra-high specific surface area.
[0104] Example 4
[0105] ⑴Heavy metal enrichment process: Prepare 1L of heavy metal mother solution (concentrations: FeCl3·6H2O 100mg / L, MnCl2·6H2O 50mg / L, NiCl2·6H2O 10mg / L and ZnSO4·7H2O 10mg / L) and add it to sterilized seawater f / 2 culture medium (the content of NaNO3 in seawater f / 2 culture medium is 74.8mg / L, the content of NaH2PO4 is 4.4mg / L, and other components are not added) to obtain 10L of experimental seawater. The seaweed is placed in the experimental seawater for 5 months, and the incubator is set with appropriate temperature (25℃), light cycle (12h:12h), and light intensity (4000lx). After the enrichment process, seaweed raw materials rich in endogenous metals can be obtained.
[0106] (2) Acid treatment: Soak the salvaged Enteromorpha in clean water, remove scale and impurities, dry, crush, pass through a 40-mesh sieve, and then put it into a sealed bag for later use; soak the seaweed powder in 0.5 mol / L hydrochloric acid solution, and hydrothermally treat it at 60°C for 12 hours, wash it with deionized water until it is neutral, and put it into an oven for drying.
[0107] ⑶ Preliminary carbonization treatment: The seaweed powder was placed in a tubular furnace for carbonization, and the temperature was raised to 800°C at a heating rate of 10°C / min for carbonization for 2 hours. After cooling to room temperature, the powder was taken out to obtain a preliminary carbonized product.
[0108] (4) Chemical regulation treatment: dry-mix the preliminary carbonization product with KOH activator in a mass ratio of (1:3), place the mixture in a tubular furnace, and heat it to a carbonization final temperature of 800°C under nitrogen protection for 2 hours at a heating rate of 5°C / min and a nitrogen flow rate of 100 mL / min. Take out the sample when it cools to room temperature.
[0109] ⑸ Washing and drying: The carbonized product is placed in a hydrochloric acid solution with a concentration of 0.1 mol / L for washing, and then filtered and continued to wash for a total of three times; then washed with deionized water in a water bath at 80°C until the pH of the washing solution is 6-8, dried, and ball-milled to obtain a natural photocatalyst A4 with an ultra-high specific surface area.
[0110] Example 5
[0111] ⑴Heavy metal enrichment process: Prepare 1L of heavy metal mother solution (concentrations: FeCl3·6H2O 100mg / L, MnCl2·6H2O 50mg / L, NiCl2·6H2O 10mg / L and ZnSO4·7H2O 10mg / L) and add it to sterilized seawater f / 2 culture medium (the content of NaNO3 in seawater f / 2 culture medium is 74.8mg / L, the content of NaH2PO4 is 4.4mg / L, and other components are not added) to obtain 10L of experimental seawater. The seaweed is placed in the experimental seawater for 5 months, and the incubator is set with appropriate temperature (25℃), light cycle (12h:12h), and light intensity (4000lx). After the enrichment process, seaweed raw materials rich in endogenous metals can be obtained.
[0112] (2) Acid treatment: Soak the salvaged Enteromorpha in clean water, remove scale and impurities, dry, crush, pass through a 40-mesh sieve, and then put it into a sealed bag for later use; soak the seaweed powder in 0.3 mol / L hydrochloric acid solution, and hydrothermally treat it at 60°C for 12 hours, wash it with deionized water until it is neutral, and put it into an oven for drying.
[0113] ⑶ Preliminary carbonization treatment: The seaweed powder was placed in a tubular furnace for carbonization, and the temperature was raised to 900°C at a heating rate of 10°C / min for carbonization for 2 hours. After cooling to room temperature, the powder was taken out to obtain a preliminary carbonized product.
[0114] (4) Chemical regulation treatment: dry-mix the preliminary carbonization product with KOH activator in a mass ratio of (1:1), place the mixture in a tubular furnace, and heat it to a carbonization final temperature of 800°C under nitrogen protection for 2 hours at a heating rate of 5°C / min and a nitrogen flow rate of 100 mL / min. Take out the sample when it cools to room temperature.
[0115] ⑸ Washing and drying: The carbonized product is placed in a 0.1 mol / L hydrochloric acid solution for washing, and then filtered and continued to wash for a total of three times; then washed with deionized water in a water bath at 80°C until the pH of the washing solution is 6-8, dried, and ball-milled to obtain a natural photocatalyst A5 with an ultra-high specific surface area.
[0116] Example 6
[0117] (1) Heavy metal enrichment process: Prepare 1L of heavy metal mother solution (concentration: FeCl3·6H2O 100mg / L) and add it to sterilized seawater f / 2 culture medium (NaNO3 content is 74.8mg / L, NaH2PO4 content is 4.4mg / L, and other components are not added) to obtain 10L of experimental seawater. The seaweed is placed in the experimental seawater for 5 months, and the incubator is set with appropriate temperature (25℃), light cycle (12h:12h), and light intensity (4000lx). After the enrichment process, seaweed raw materials rich in endogenous metals can be obtained.
[0118] (2) Acid treatment: Soak the salvaged Enteromorpha in clean water, remove scale and impurities, dry, crush, pass through a 20-mesh sieve, and then put it into a sealed bag for later use; soak the seaweed powder in 0.1 mol / L hydrochloric acid solution, and hydrothermally treat it at 40°C for 12 hours, wash it with deionized water until it is neutral, and put it into an oven for drying.
[0119] ⑶ Preliminary carbonization treatment: The seaweed powder was placed in a tubular furnace for carbonization, and the temperature was raised to 1000°C at a heating rate of 15°C / min for carbonization for 2 hours. After cooling to room temperature, it was taken out to obtain a preliminary carbonized product.
[0120] (4) Chemical regulation treatment: dry-mix the preliminary carbonization product with KOH activator in a mass ratio of (1:1), place the mixture in a tubular furnace, and heat it to a carbonization final temperature of 800°C under nitrogen protection for 2 hours at a heating rate of 5°C / min and a nitrogen flow rate of 100 mL / min. Take out the sample when it cools to room temperature.
[0121] ⑸ Washing and drying: The carbonized product is placed in a hydrochloric acid solution with a concentration of 0.1 mol / L for washing, and then filtered and continued to wash for a total of three times; then washed with deionized water in a water bath at 80°C until the pH of the washing solution is 6-8, dried, and ball-milled to obtain a natural photocatalyst A6 with an ultra-high specific surface area.
[0122] Comparative Example 1
[0123] (1) Heavy metal enrichment process: Prepare 1L of heavy metal mother solution (concentration: FeCl3·6H2O 100mg / L) and add it to sterilized seawater f / 2 culture medium (NaNO3 content is 74.8mg / L, NaH2PO4 content is 4.4mg / L, and other components are not added) to obtain 10L of experimental seawater. The seaweed is placed in the experimental seawater for 5 months, and the incubator is set with appropriate temperature (25℃), light cycle (12h:12h), and light intensity (4000lx). After the enrichment process, seaweed raw materials rich in endogenous metals can be obtained.
[0124] (2) Pretreatment: Soak and clean the salvaged Enteromorpha with clean water, remove scale and impurities, dry, crush, pass through an 80-mesh sieve, and then put it into a sealed bag for later use.
[0125] ⑶ Preliminary carbonization treatment: The seaweed powder was placed in a tubular furnace for carbonization, and the temperature was raised to 700°C at a heating rate of 5°C / min for carbonization for 2 hours. After cooling to room temperature, the powder was taken out to obtain a preliminary carbonized product.
[0126] (4) Chemical regulation treatment: dry-mix the preliminary carbonization product with KOH activator in a mass ratio of (1:3), place the mixture in a tubular furnace, and heat it to a carbonization final temperature of 800°C under nitrogen protection for 2 hours at a heating rate of 5°C / min and a nitrogen flow rate of 100 mL / min. Take out the sample when it cools to room temperature.
[0127] ⑸ Washing and drying: The carbonized product is placed in a 0.1 mol / L hydrochloric acid solution for washing, and then filtered and washed three times in total; then washed with deionized water in a 80°C water bath until the pH of the washing solution is 6-8, dried, and ball-milled to obtain the natural photocatalyst D1.
[0128] Comparative Example 2
[0129] (1) Heavy metal enrichment process: Prepare 1L of heavy metal mother solution (concentration: FeCl3·6H2O 100mg / L) and add it to sterilized seawater f / 2 culture medium (NaNO3 content is 74.8mg / L, NaH2PO4 content is 4.4mg / L, and other components are not added) to obtain 10L of experimental seawater. The seaweed is placed in the experimental seawater for 5 months, and the incubator is set with appropriate temperature (25℃), light cycle (12h:12h), and light intensity (4000lx). After the enrichment process, seaweed raw materials rich in endogenous metals can be obtained.
[0130] (2) Acid treatment: Soak the salvaged Enteromorpha in clean water, remove scale and impurities, dry, crush, pass through an 80-mesh sieve, and then put it into a sealed bag for later use; soak the seaweed powder in 0.5 mol / L hydrochloric acid solution, and hydrothermally treat it at 60°C for 12 hours, wash it with deionized water until it is neutral, and put it into an oven for drying.
[0131] ⑶ Chemical regulation treatment: dry-mix seaweed powder and KOH activator in a mass ratio of (1:3), place the mixture in a tubular furnace, and heat to a carbonization final temperature of 800°C under nitrogen protection for 2 hours at a heating rate of 5°C / min and a nitrogen flow rate of 100 mL / min. Take out the sample when it cools to room temperature.
[0132] (4) Washing and drying: The carbonized product is placed in a 0.1 mol / L hydrochloric acid solution for washing, and then filtered and washed three times in total; then washed with deionized water in a 80°C water bath until the pH of the washing solution is 6-8, dried, and ball-milled to obtain the natural photocatalyst D2.
[0133] Comparative Example 3
[0134] (1) Heavy metal enrichment process: Prepare 1L of heavy metal mother solution (concentration: FeCl3·6H2O 50mg / L) and add it to sterilized seawater f / 2 culture medium (NaNO3 content is 74.8mg / L, NaH2PO4 content is 4.4mg / L, and other components are not added) to obtain 10L of experimental seawater. The seaweed is placed in the experimental seawater for 5 months, and the incubator is set with appropriate temperature (25℃), light cycle (12h:12h), and light intensity (4000lx). After the enrichment process, seaweed raw materials rich in endogenous metals can be obtained.
[0135] (2) Acid treatment: Soak the salvaged Enteromorpha in clean water, remove scale and impurities, dry, crush, pass through an 80-mesh sieve, and then put it into a sealed bag for later use; soak the seaweed powder in 0.5 mol / L hydrochloric acid solution, and hydrothermally treat it at 60°C for 12 hours, wash it with deionized water until it is neutral, and put it into an oven for drying.
[0136] ⑶ Preliminary carbonization treatment: The seaweed powder was placed in a tubular furnace for carbonization, and the temperature was raised to 700°C at a heating rate of 5°C / min for carbonization for 2 hours. After cooling to room temperature, the powder was taken out to obtain a preliminary carbonized product.
[0137] (4) Washing and drying: The preliminary carbonized product is placed in a 0.1 mol / L hydrochloric acid solution for washing, and then filtered and washed three times in total; then washed with deionized water in a 80°C water bath until the pH of the washing solution is 6-8, dried, and ball-milled to obtain the natural photocatalyst D3.
[0138] Comparative Example 4
[0139] ⑴ Acid treatment: Soak the salvaged Enteromorpha in clean water, remove scale and impurities, dry, crush, pass through an 80-mesh sieve, and then put it in a sealed bag for use; soak the seaweed powder in 0.5 mol / L hydrochloric acid solution, and hydrothermally treat it at 60°C for 12 hours, wash it with deionized water until it is neutral, and put it in an oven to dry.
[0140] (2) Preliminary carbonization treatment: The seaweed powder was placed in a tubular furnace for carbonization, and the temperature was raised to 700°C at a heating rate of 5°C / min for carbonization for 2 hours. After cooling to room temperature, the powder was taken out to obtain a preliminary carbonized product.
[0141] ⑶ Chemical regulation treatment: dry-mix the preliminary carbonization product with KOH activator in a mass ratio of (1:3), place the mixture in a tubular furnace, and heat it to a carbonization final temperature of 800°C under nitrogen protection for 2 hours at a heating rate of 5°C / min and a nitrogen flow rate of 100 mL / min. Take out the sample when it cools to room temperature.
[0142] (4) Washing and drying: The carbonized product is placed in a 0.1 mol / L hydrochloric acid solution for washing, and then filtered and washed three times in total; then washed with deionized water in a 80°C water bath until the pH of the washing solution is 6-8, dried, and ball-milled to obtain the natural photocatalyst D4.
[0143] Adsorption-degradation test of organic dyes by natural photocatalysts
[0144] The photocatalytic activity of natural photocatalysts under visible light was analyzed using methylene blue, a typical organic dye, as the target pollutant. 0.02 g of photocatalyst was dispersed in 40 mL of a 40 mg / L dye solution, and the reaction solution was placed in the dark for 1 h to achieve an adsorption-desorption equilibrium state between the photocatalyst and the dye molecules. The absorbance at the maximum absorption wavelength (664 nm) was detected using a UV-visible spectrophotometer. In order to evaluate the adsorption performance of the prepared photocatalyst, the equilibrium adsorption capacity was calculated as follows:
[0145] Adsorption(%)=[(A0-A1) / A0]×100%
[0146] Where A0 is the initial absorbance of the dye molecule and A1 is the absorbance measured at the equilibrium time.
[0147] The suspension was stirred at room temperature (25°C) and cooled by a circulating water system. 2 mL of the mixture was taken at specific time intervals using a pipette and then centrifuged at 8000 r / min for 10 min. The supernatant of the dye solution was collected and analyzed using a UV-visible spectrophotometer.
[0148] The degradation efficiency was determined as follows:
[0149] Degradation(%)=[(A1-A t ) / A1]×100%
[0150] Where t is a specific time, A t is the absorbance of the dye at a specific time.
[0151] Recycling experiment
[0152] In order to explore the practical application potential of photocatalysts, the reaction stability of natural photocatalysts was evaluated by evaluating the degradation performance of organic dyes in four consecutive cycles. Under dark conditions, 0.02 g of natural photocatalyst was dispersed in 40 mL, 40 mg / L cationic dye solution for 1 h to achieve the adsorption-desorption equilibrium state between the photocatalyst and the organic dye molecules, and then the suspension was further exposed to a visible light source for a period of time. The removal performance of the prepared natural photocatalyst was detected using a UV-visible spectrophotometer at an absorption wavelength of 664 nm. After equilibrium, the sample was stirred and washed, and then reused in the next three cycles.
[0153] Figure 1 This is a SEM image of the seaweed raw material at low magnification. Figure 2 This is a SEM image of the seaweed raw material at high magnification. It can be seen that the surface of the seaweed raw material is relatively smooth and flat, showing a large block morphology, and no obvious pore structure is observed.
[0154] Figure 3 The SEM images of the natural photocatalysts prepared in Examples 1 to 6 are as follows: Figure 3 (a) to (f) correspond to A1 to A6 respectively. It can be seen that the activator effectively etches the carbon skeleton of the photocatalyst, and there are many surface defect structures, showing an obvious pore structure. These well-developed pore structures and rich surface defect structures give the photocatalyst a higher specific surface area, which is beneficial to improving the adsorption and photocatalytic degradation activity.
[0155] Figure 4 The SEM images of the natural photocatalysts prepared in Comparative Examples 1 to 4 are shown in FIG. Figure 4 (g) to (j) correspond to D1 to D4, respectively. It can be seen that the photocatalyst prepared in the comparative example has fewer defects and irregular pore structure development.
[0156] Figure 5 is the N2 adsorption-desorption isotherm of natural photocatalyst A1; Figure 6 This is the pore size distribution diagram of natural photocatalyst A1. It can be seen that the sample contains a certain number of microporous structures and quite rich mesoporous structures.
[0157] Figure 7 The figure shows the removal effect of natural photocatalysts A1-A6, D1-D4 and CB (blank control) on organic dyes. It can be seen that the photocatalytic degradation activity is A1>A3>A4>A5>A2>A6, D1>D2>D3>D4>CB, indicating that the rich specific surface area and metal mineral template are conducive to the photocatalytic degradation of pollutants, and under the condition of no biological enrichment treatment, the efficiency of photocatalytic degradation of pollutants is significantly reduced; Figure 8This is a cyclic experiment of natural photocatalyst A1 degrading methylene blue. It can be seen that through the investigation of the photocatalyst's photolysis performance of target pollutants after 1 hour of dark adsorption and 2 hours of catalysis under visible light, it was found that the removal efficiency of natural photocatalyst A1 for organic dyes is nearly 100%; after 4 cycles, the photocatalyst still has good pollutant removal performance.
[0158] The specific surface area of the natural photocatalyst of the present invention was tested, and the results are shown in Table 1. It can be seen that the natural photocatalyst prepared by the present invention has a high specific surface area and is rich in endogenous mineral components, such as Fe, Mn, Ti, Zn or Ni, which can improve the graphitization level of the catalyst during pyrolysis, promote the formation of edge defect structures, and significantly improve the electron transfer ability, which lays a theoretical foundation for preparing it into a natural, endogenous foam carbon photocatalyst.
[0159] Table 1 Specific surface area parameters of photocatalysts prepared in different embodiments and comparative examples
[0160] sample <![CDATA[Specific surface area (m 2 / g)]]> Average pore size (nm) EP 1.99 4.92 A1 3360.28 2.41 A2 1648.20 2.61 A3 3026.18 2.14 A4 2546.37 2.23 A5 1696.59 2.29 A6 1438.12 2.67 D1 827.98 2.87 D2 596.17 2.99 D3 387.61 3.95 D4 859.78 2.81
[0161] Table 2 shows the contents of main non-metallic elements in seaweed raw materials.
[0162] Table 2 Main non-metallic elements in seaweed raw materials
[0163]
[0164] Table 3 shows the contents of main metal elements in seaweed raw materials measured by ICP method.
[0165] Table 3 Main metal element contents in seaweed raw materials measured by ICP method
[0166]
[0167] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a natural photocatalyst with ultra-high specific surface area, characterized in that: The following steps are involved: The seaweed is placed in a heavy metal polluted water body for cultivation to obtain seaweed rich in endogenous metals; Expanding the endogenous metal-rich seaweed in sections to obtain a preliminary carbonized product; The preliminary carbonization product is mixed with an activator and then subjected to chemical regulation treatment to obtain a carbonization product; The carbonized product is washed and dried in sequence to obtain the natural photocatalyst.
2. The preparation method according to claim 1, characterized in that: The heavy metal elements in the heavy metal polluted water body include one or more of Fe, Mn, Ni and Zn.
3. The preparation method according to claim 1, characterized in that: The segmented hole expansion includes acid treatment and preliminary carbonization treatment in sequence, and the acid treatment includes acid immersion and hydrothermal treatment in sequence.
4. The preparation method according to claim 3, characterized in that: The acid reagent used in the acid soaking is a hydrochloric acid solution or a nitric acid solution.
5. The preparation method according to claim 3, characterized in that: The temperature of the hydrothermal treatment is 20-80° C. and the time is 12-24 hours.
6. The preparation method according to claim 3, characterized in that: The temperature of the preliminary carbonization treatment is 600-1000° C., the insulation time is 1-3 hours, and the heating rate from room temperature to the temperature of the preliminary carbonization treatment is 5-15° C. / min.
7. The preparation method according to claim 1, characterized in that: The mass ratio of the activator to the preliminary carbonization product is 1 to 5:
1.
8. The preparation method according to claim 1, characterized in that: The temperature of the chemical regulation treatment is 600-1000°C, the insulation time is 1-3h, the heating rate from room temperature to the temperature of the chemical regulation treatment is 5-15°C / min, and the chemical regulation treatment is carried out in a protective atmosphere.
9. A natural photocatalyst with ultra-high specific surface area obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the natural photocatalyst with ultra-high specific surface area as claimed in claim 9 in the treatment of organic dye wastewater.
Citation Information
Patent Citations
Method for preparing biomass activated carbon through vacuum freeze drying
CN106809834A
Preparation method and application of biochar by enriching copper element in ciliate desert grass
CN109850887A
Method for removing heavy metals in water by utilizing marine microalgae
CN112707509A
Seaweed biochar ZnO photocatalyst and preparation method thereof
CN117753401A